Conspicuous consumption and communism: Evidence from East and West Germany - Tim Friehe; Mario Mechtel (University of Trier, Institute for Labour Law and Industrial Relations in the European Union (IAAEU), 2012)
This paper investigates the influence of the political regime on the relative importance of conspicuous consumption. We use the separation of Germany into the communist GDR and the democratic FRG and its reunification in 1990 as a natural experiment. Relying on household data that are representative for Germany, our empirical results strongly indicate that conspicuous consumption is relatively more important in East Germany. Importantly, a significant gap in conspicuous consumption expenditures remains even 18 years after the reunification.
Keywords: D12; D62; P36; 330; conspicuous consumption; status-seeking; relative income; political regime; behavioral economics; Konsuminterdependenz; Konsumentenverhalten; Politisches System; Vergleich; Neue Bundesländer; Deutschland; DDR